Using Brainstorming Technique in Speaking Activity for Senior High School Students - Tuti Srihandayani; Leni Marlina (Universitas Negeri Padang, 2019)
AbstractMany EFL students tend to have difficulties in speaking practice related to a recount text, such as no interest in speaking; lack of grammar and vocabulary; lack of background knowledge and do not know how to pronounce the word; inappropriate technique in teaching and learning process. Considering such problems, an appropriate teaching technique is needed to help students improve their ability in speaking practice related to a recount text. Brainstorming technique is the technique that makes students active to convey the idea about the topic spontaneously in learning classroom. This paper aims to explain how to implement a brainstorming technique in speaking activity especially in recount text (personal recount). It also aims to encourage and motivate students’ speaking activity in front of the class. Brainstorming technique is conducted by making several groups to be four students. After that, the teacher asks the students to brain and storm the list of ideas in a small group by using mind mapping and story mapping.The students use mind mapping as an alarm word about the topic that happened in the past by finding the keyword in small group. After that, the students use story mapping to develop the word into story by creating the main idea. Finally, the students present the recount text (personal recount) in front of the class. Futhermore, brainstorming technique can be an alternative technique in speaking activity related to a recount text.Key words: Brainstorming Technique, Mind Mapping, Story Mapping, Speaking, Recount Text.